Health Inequality / An Introduction to Theories, Concepts and Methods - Bartley Mel; Polity (2004)
This book provides all things about health inequality. Acknowledgements, What is Health Inequality, Measuring Socio-Economic Position, Figuring Out Health Inequality, Models of Etiological Pathways I: Behavioral and ''Cultural'' Explanations, Models of Etiological Pathways II: The Psycho-Social Model, Models of Etiological Pathways III: The Materialist Model, Models of Etiological Pathways IV: The Life Course Approach, Social Ecology, Gender Inequality in Health, Ethnic Inequalities in Health, Health Inequality and Social Policy, References, Index.